Christian Allegory in Early Hispanic Poetry - Foster, David William (Book collections on Project MUSE., 1971)
Distinguishing figural or typological allegory -- a method adapted from the Christian exegesis of the Old Testament -- from the broader Hellenistic concept of allegory, this book examines its use in representative poems of early Hispanic literature. The author focuses on the thematic and structural employment of this originally nonliterary device and comments on the literary problems it posed and the artistic effects which were achieved by it. The development of this particular allegorical method in medieval Hispanic literature -- works in Spanish, Portuguese, Galician, and Catalan -- he shows.